2020
DOI: 10.1016/j.jhazmat.2020.122532
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of pyoverdines in iron removal from flocking asbestos waste: An innovative bacterial bioremediation strategy

Abstract: The use of asbestos-containing products has been banned in many countries since the beginning of the 80's due to its carcinogenic properties. However, asbestos is widely present in private and public buildings, resulting in the need to process a vast amount of asbestos-containing waste. Among the current technologies for the destruction of asbestos fibers, biodegradation by fungi, lichens, and, more recently, bacteria has been described. We previously reported the involvement of the bacterial siderophore pyove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…Interestingly, David et al [72,80] showed a large decrease of iron content in asbestos fibers after long-term alteration with PVDs and confirmed the active dissolution by the siderophores (Figure 8). This process of bioweathering could lead to a reduction in asbestos toxicity.…”
Section: Asbestos Waste Dissolution By Pyoverdinesmentioning
confidence: 69%
See 4 more Smart Citations
“…Interestingly, David et al [72,80] showed a large decrease of iron content in asbestos fibers after long-term alteration with PVDs and confirmed the active dissolution by the siderophores (Figure 8). This process of bioweathering could lead to a reduction in asbestos toxicity.…”
Section: Asbestos Waste Dissolution By Pyoverdinesmentioning
confidence: 69%
“…Recently, studies of David et al [72,[78][79][80] corroborate that these siderophores are also involved in the dissolution of other silicate minerals such as asbestiform minerals. Indeed, asbestos is an iron source for various microorganisms.…”
Section: Role Of Pyoverdine and Pyochelin In Asbestos Weatheringmentioning
confidence: 92%
See 3 more Smart Citations